Respon Kombinasi Pemberian Pupuk Kompos Kotoran Kambing dan Ekstrak Bioska Terhadap Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogaea L) - Sitorus, Andika; Mardiana, Siti (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This study aims to examine the response of the growth and production of peanuts (Arachis hypogaea L.) to the combination of fertilizer application, goat manure, manure and bioska extract. The study used a factorial Group Random Design (RAK) with two factors, namely the dose of goat dung compost (0, 2, and 4 tons/ha) and the concentration of bioska extract (0%, 1%, and 2%). The results of the study showed that the combination of applying compost, goat manure and bioska extract had a significant influence on the vegetative growth and components of peanut crops. The combination of 4 tons/ha goat dung compost and 2% bioska extract gives the best results, increasing plant height, number of leaves, leaf area, number of pods, number of seeds, seed weight, harvest index, and total biomass weight. This increase is thought to be due to increased soil fertility, growth stimulation by cinema, and the synergistic effects of a combination of the two. Analysis of soil and plant nutrients showed an increase in the availability and uptake of nutrients, as well as an increase in the chlorophyll content of the leaves.